2023
DOI: 10.1098/rspb.2023.1338
|View full text |Cite
|
Sign up to set email alerts
|

Urban birds become less fearful following COVID-19 reopenings

Eleanor S. Diamant,
Ian MacGregor-Fors,
Daniel T. Blumstein
et al.

Abstract: Following the COVID-19 pandemic, many people around the world stayed home, drastically altering human activity in cities. This exceptional moment provided researchers the opportunity to test how urban animals respond to human disturbance, in some cases testing fundamental questions on the mechanistic impact of urban behaviours on animal behaviour. However, at the end of this ‘anthropause', human activity returned to cities. How might each of these strong shifts affect wildlife in the short and long term? We fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Firstly, wildlife in urban spaces may become more tolerant of human presence as time progresses. For example, recent research has found that birds in urban spaces have been less fearful of humans following the COVID-19 pandemic (Diamant et al 2023). Our target species are also known to be common in urban spaces, meaning that they likely have higher tolerances to human presence and activity.…”
Section: Discussionmentioning
confidence: 95%
“…Firstly, wildlife in urban spaces may become more tolerant of human presence as time progresses. For example, recent research has found that birds in urban spaces have been less fearful of humans following the COVID-19 pandemic (Diamant et al 2023). Our target species are also known to be common in urban spaces, meaning that they likely have higher tolerances to human presence and activity.…”
Section: Discussionmentioning
confidence: 95%